Gerhard Kubik lectures (International Library of African Music, 1969)
The German Cultural Institutes (Goethe-Institutes) have invited Gerhard Kubik to give a series of lectures on African Music in various West African Towns (in Cameroun, Nigeria, Dahomey, Togo and Ghana), in Winter 1969/70.
Keywords: African Music